PENGARUH BUDAYA ORGANISASI TERHADAP EFEKTIFITAS KERJA PEGAWAI - Yohana Kartika; Herlina Herlina; Sri Utami Humairoh Wirba; Abdul Miad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
Organizational culture is a shared value system regarding important things and is a belief about how an organization works. In this way, organizational culture provides a framework that organizes and guides the behavior of organizational members at work. This research was conducted by giving a questionnaire to 53 respondents, each respondent answered 10 questions. Then carried out several tests, from the results of the study showed that the organizational culture simultaneously had a significant effect on the work effectiveness of employees in working at the Public Works and Public Housing Training Center Region I Medan.